(untitled) (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Malaria is an infection caused by Plasmodium through female Anopheles bites. Malaria affects almost all components of the blood cells. Decreased of hemoglobin levels in malaria infection caused by hemolysis of red blood cells and lack of ferrin due to the entry of Plasmodium sp. into the erythrocytes while the decrease in the number of platelets is due to the destruction of platelets by macrophages in the spleen. The aim of the study was to determine the correlation between malaria infection and hemoglobin levels and platelet counts at the dr. Soedibjo Sardadi Jayapura hospital. This type of research used analytic observational techniques by cross sectional design. The study sample were malaria sufferers who met the inclusion and exclusion criteria was then examined for hemoglobin levels and platelet counts of 48 respondents. Study result showed that the average hemoglobin level in malaria sufferers is 10.5 gdl-1 with the Spearman correlation test result 0.171 (>0.05). The average number of platelets in malaria sufferers is 127,000/mm³ with Spearman correlation test result 0.003 (<0.05). The conclusion of the study was that there was no relationship between malaria infection and hemoglobin levels and there was a relationship between malaria infection and platelet counts.